Evaluation of a naturally derived tannin extracts biopolymer additive in drilling muds for high-temperature well applications - Abdul R. Ismail; M. N. A. Mohd Norddin; Nur A. S. Latefi; Jeffrey O. Oseh; Issham Ismail; Afeez O. Gbadamosi; Augustine J. Agi (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract The formulations of drilling fluids using conventional clays are often faced with difficulties in the control of rheology, filtration and gelation, owing to the flocculation of the clay at the temperature above 250 °F. In this study, tannins were extracted from the bark wastes of Rhizophora Mucronata spp. (RMTE) and used as a deflocculant to formulate water-based muds (WBMs). The efficacy of reducing the gelation and viscosity of WBMs with the extracted RMTE was compared with commercial Modified Desco Tannin (MDT). The RMTE was characterized using Fourier-transform infrared spectroscopy (FTIR). Rheological and filtration control properties tests were conducted on the RMTE and MDT mud samples before and after hot rolling tests at different temperatures of 225 °F, 250 °F, 275 °F and 300 °F. FTIR test data indicate the presence of different active functional groups in the RMTE structure, especially the hydroxyl (–OH) groups, which are responsible for the good thinning ability of the RMTE. Experimental data of the WBM after hot rolling tests with 8 g concentration at 300 °F show a 43.5% reduction of plastic viscosity with MDT and 50% reduction with RMTE. With a concentration of 2 g, the yield point of the WBM with commercial MDT and locally derived RMTE at 225 °F before hot rolling tests reduced by 50% and 57.1%, respectively. Furthermore, the addition of RMTE and MDT to the WBM reduced the filtrate volume and the gel strength. The experimental data indicate that the RMTE shows better deflocculating performance compared to that of the MDT, illustrating the need for its application in WBMs for high-temperature wells.